Spatial configuration Based on Relationship between Buildings and Road Network in Kupang City, East Nusa Tenggara Province, Indonesia - Salsabila Tuhfah, Khoirunnisa; Farida Azzahra Arifin , Aqilla; Izdhihar, Muhammad Faza; Tallo, Amandus Jong (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Oebobo District has the highest density level among all sub-districts in Kupang City. The impact of population growth and circulation is that the mobility of people and goods often occurs quickly, thus hampering efficient observation. This research highlights the need for accurate recognition to develop recommended effective and optimal space management and utilization. The focus of this research is population movement patterns by considering spatial structure. Quantitative descriptive research method used over the space syntax approach on QGIS and DepthMapX softwares. Quantification is carried out on the connectivity value to measure the level of connection in the road network and the integration value to reflect the integration between spaces. With the highest connectivity and integration scores, Oebobo District has the potential to become the city center or main activity center in Kupang City.